2016
DOI: 10.21608/adjalexu.2016.58039
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Panoramic X-Ray Versus Cone Beam Computerized Tomography in Surgical Removal of Horizontally Impacted Mandibular Third Molars

Abstract: INTRODUCTION: Computerized scanning technology has been in use for 30 years. Originally, it was called Computerized Axial Tomography or CAT. Today, with advances in miniaturization and computer software and a revolution in imaging, CAT scan technology has been moved from the hospital to the private dental office in the form of Cone Beam Computerized Tomography (CBCT), which will be an alternative radiographic study over the standard panoramic images. OBJECTIVES: This study evaluated the advantage of CBCT over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 19 publications
0
15
0
3
Order By: Relevance
“…Unfortunately, conventional x-rays, periapical and panoramic radiographs to exemplify, can simply offer restrained anatomical data and facts in relation to approximation of IAN to the 3rd molars, including and their association to the IAN canals. 8,11 A comparison of the computed tomographic scan and panoramic radiography before mandibular third molar extraction surgery was done by Luo et al 12 They aptly demonstrated that preoperative panoramic radiography, Computed Tomography (CT) scan, age, and the expertise of the health care provider can influence commonly expected postoperative sequelae after extraction of a mandibular 3rd molar. Panoramic radiography by itself is not sufficient to predict hypoesthesia of lips and/or chin.…”
Section: Panoramic Radiographymentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, conventional x-rays, periapical and panoramic radiographs to exemplify, can simply offer restrained anatomical data and facts in relation to approximation of IAN to the 3rd molars, including and their association to the IAN canals. 8,11 A comparison of the computed tomographic scan and panoramic radiography before mandibular third molar extraction surgery was done by Luo et al 12 They aptly demonstrated that preoperative panoramic radiography, Computed Tomography (CT) scan, age, and the expertise of the health care provider can influence commonly expected postoperative sequelae after extraction of a mandibular 3rd molar. Panoramic radiography by itself is not sufficient to predict hypoesthesia of lips and/or chin.…”
Section: Panoramic Radiographymentioning
confidence: 99%
“…It gives a much-decreased dose of radiation to the patient, has a low cost as compared to conventional CT, gives a higher quantity reconstruction and high-precision bone details. 5,8 With CBCT, the impacted 3 r d molar may be visible in numerous views (coronal, sagittal, axial or horizontal), which is obviously lacking in the panoramic view. This makes it feasible to attain the correct vicinity of the impacted 3 r d molar, and its relation to the adjoining IAN.…”
Section: Cone Beam Ctmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, the DF is considered normal when its maximum width is lower than 2.5 mm [3][4][5][6][7][8][9][11][12][13][14]22,23]. At present, it is increasingly common to have a pre-surgical evaluation using tridimensional radiographic exams (e.g., cone beam computer tomography, CBCT) [22,[24][25][26][27][28][29][30][31][32][33][34]. Because of the low dosage of X-rays associated with this method, it represents the foremost technique administered in pediatric patients [35,36].…”
Section: Introductionmentioning
confidence: 99%